2022
DOI: 10.2147/ccid.s385376
|View full text |Cite
|
Sign up to set email alerts
|

The Relevant of Sex Hormone Levels and Acne Grades in Patients with Acne Vulgaris: A Cross-Sectional Study in Beijing

Abstract: Background The tests of sex hormones play pivotal roles in the clinical diagnosis and treatment of acne vulgaris, but the majority of patients with acne vulgaris present regular sex hormone levels within the normal reference range. Objective To determine the correlation among levels of sex hormones, ratio of androgen to estrogen and acne grades in patients with acne vulgaris. Methods A cross-sectional study was applied to collect 693 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The study by Dhaher et al showed an elevated LH/FSH ratio in up to 25% of patients, although all patients had previously been diagnosed with PCOS [33]. The result of the study presented by Zhang et al confirmed a correlation between elevated levels of FSH and the severity of acne [24]. In our study, statistical analysis also revealed higher mean ± SD FSH serum levels in acne patients compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The study by Dhaher et al showed an elevated LH/FSH ratio in up to 25% of patients, although all patients had previously been diagnosed with PCOS [33]. The result of the study presented by Zhang et al confirmed a correlation between elevated levels of FSH and the severity of acne [24]. In our study, statistical analysis also revealed higher mean ± SD FSH serum levels in acne patients compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 85%
“…The result of the study presented by Zhang et al . confirmed a correlation between elevated levels of FSH and the severity of acne [ 24 ]. In our study, statistical analysis also revealed higher mean ± SD FSH serum levels in acne patients compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent evidence shows that systemic and distant factors may have an influence on acne as well. Some examples include noted associations with circulating androgens [ 5 , 6 , 7 ], shifts in circulating short-chain fatty acids [ 8 ], and shifts in the gut microbiome [ 9 ]. In particular, previous studies have noted that circulating hormones such as testosterone, progesterone, dihydrotestosterone, and estrogen modulate acne [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The direct inhibitory effect of androgens on inflammation arises from the activation of overlapping signalling pathways, mainly the ERK-1 or ERK-2 pathway, which ultimately modulate the expression and activity of inflammatory mediators, including the cytokines TNF-α and IL-1β as well as the C-reactive protein [ 17 , 18 ]. It has also been shown that increasing the androgen/estrogen ratio can exacerbate the severity of acne in patients with acne vulgaris [ 19 ]. In addition, sebaceous gland activity is influenced by the growth hormone, insulin, cortisol, prolactin, thyroid hormones, and adrenaline.…”
Section: Introductionmentioning
confidence: 99%